Experimental evaluation of the effect of a territorial damselfish on foraging behaviour of roving herbivores on coral reefs - Eurich, Jacob G.; Shomaker, Simone M.; McCormick, Mark I.; Jones, Geoffrey P. (Journal of experimental marine biology and ecology, 2018)
Roving herbivorous fishes play an important role in coral reef communities by removing turf-algae, which can facilitate the settlement of coral larvae. Territorial damselfishes can influence the foraging patterns of roving herbivores by excluding them from their territories, altering the benthic assemblage. However, the impacts depend on the intensity of aggression and which taxonomic groups of roving herbivores are being excluded. Here we document the foraging activity of roving herbivores (Acanthuridae, Scaridae, Siganidae) and the extent to which they are subject to aggression by Pomacentrus adelus, the most abundant territorial damselfish in Kimbe Bay, Papua New Guinea. We then conducted experimental removals (220 m2 plots on the reef flat) of P. adelus to examine its impact on roving herbivores and the benthic community structure. We hypothesized that the removal of P. adelus would lead to an increase in roving herbivore abundance and foraging activity and a decline in algal cover. The relative abundance (MaxN) and foraging activity (bite rate) of each taxa were examined pre and post-removal using video quadrats. The overall relative abundance of roving herbivores was not influenced by the removal of P. adelus. No changes in foraging patterns were observed for parrotfish, the family that received the highest rate of agonistic interactions, and rabbitfish. The removal of P. adelus resulted in a significant decrease in surgeonfish feeding, suggesting P. adelus alters foraging patterns indirectly through territorial maintenance and not aggression. The only measurable benthic impact of the P. adelus removal was an increase in sediment, while all other substratum types remained constant. These results indicate that P. adelus does not have a negative impact on all roving herbivores and instead may contribute to surgeonfish foraging indirectly through the removal of sediment. The generalisation that territorial damselfish reduce foraging rates of roving herbivores may not be applicable in all systems or for all species. •Abundance of herbivores was not affected by removal of a territorial damselfish.•No changes in foraging patterns were observed for parrotfish and rabbitfish.•Removal of P. adelus resulted in a significant decrease in surgeonfish feeding.•Sediment loads increased on reefs where territorial damselfish were removed.•Territorial damselfish may not always have an adverse effect on roving herbivores.